Anthropogenic and Climate Change Impacts on Diwaniya River Water Quality - Saraa M. Ali; Mohammed S. Shamkhi; Zaid Abed Al-Ridah (International Journal of Computational and Experimental Science and Engineering, 2025)
This study aims investigates the calibration and validation of the HEC-RAS model to simulate critical water quality parameters in Iraq’s semi-arid environment, focusing on its application for sustainable water resource management. Using a robust dataset of observed and simulated values, the research examined biochemical oxygen demand (BOD₅), total dissolved solids (TDS), dissolved oxygen (DO), electrical conductivity (EC), nitrate (NO₃⁻), phosphate (PO₄³⁻), calcium (Ca), and magnesium (Mg). The calibration and validation results demonstrated strong alignment between observed and simulated data, with high R² values for key parameters such as NO₃⁻ (R² = 0.94 for validation) and PO₄³⁻ (R² = 0.96 for calibration), affirming the model’s reliability in predicting nutrient dynamics. The study identified variations in model accuracy, with TDS exhibiting percentage errors ranging from 1.70% to 8.73% and challenges in simulating DO, where negative errors exceeded 12%. These discrepancies reflect the complexity of modeling organic matter decomposition and oxygen dynamics under fluctuating climatic and flow conditions. Additionally, pollution hotspots characterized by elevated EC and TDS levels were detected, underscoring the significant impact of anthropogenic activities on water quality. By providing a validated framework for simulating critical water quality indicators, this study contributes to water quality modeling in arid and semi-arid regions. The findings offer valuable insights for policymakers, emphasizing the integration of advanced hydrological models with sustainable management practices. This research advocates for adaptive strategies to mitigate water quality degradation, addressing challenges posed by climate change and increasing population pressures.